A case of recurrent porocarcinoma of the scalp requiring scalp reconstruction - Puri, Gopal; Kataria, Kamal; Ranjan, Piyush; Dhar, Anita; Srivastava, Anurag (International Surgery Journal, 2020)
Eccrine porocarcinoma (EPC) is a rare malignant tumour, first reported by Pinkus and Mehregan in 1963. It can develop from the eccrine duct epithelial component or transform from an underlying eccrine poroma. The tumor usually presents as an exophytic growth and has a female predilection. Rarely it can occur in scalp, face, ear, genitalia and eye lids. Treatment modalities have included standard excision, Mohs micrographic surgery, chemotherapy, and radiation therapy. Therapy of choice is surgical excision with clear margins with 70-80% cure rates. Chemotherapy is of no known significance and radiation might help in selective cases. Majority of cases are managed with excision and closure of defects but in selective cases there may be need to reconstruct the scalp defects. The methods of reconstruction may be local flaps, free tissue transfer and partial/full thickness skin grafts. Regional flaps are very useful in patients requiring cover of large defects.